MANAJEMEN SEKOLAH TERPENCIL - Hulopi, Asri Rahayu; Suking, Arifin; Zulystiawati (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2025)
This study aims to describe the educational management process in schools located in remote or hard-to-reach areas, particularly in the remote area of Gorontalo Province, as viewed from: (1) teacher management, (2) learning, and (3) facilities and infrastructure at SMPN 1 Pinogu. This study uses a qualitative approach with a case study design. Data collection techniques used include interviews, observations, and documentation. Data analysis employs interactive data analysis, supported by data validity checks using triangulation techniques. The research findings indicate that: (1) teacher management is conducted through the recruitment and placement of local teachers with a bachelor's degree qualification, as well as training through the MGMP; (2) Learning management includes curriculum design and learning activities using lesson plans, syllabi, and competency-based learning outcomes, although the use of technology is limited due to limited internet access and electricity; and (3) Facilities and infrastructure management includes infrastructure planning through collaboration with the government and school committee, building maintenance, and management of technological equipment such as laptops and projectors that are shared among teachers.